Dinámica del cambio de cobertura y uso del suelo en los paisajes degradados en el sector alto del Río Madre de Dios 2001-2021 - Castro Medina, Walter Fidel (2025)
Environmental degradation, reflected in changes in land cover and land use, poses a global challenge, especially in developing countries like Peru. In the upper Madre de Dios River region, located in the Peruvian Amazon, significant transformations have been observed in recent decades due to massive internal migrations and anthropogenic activities. The objective of this study was to assess environmental degradation in this area during the period 2001-2021 based on indicators of land cover and land use change and change intensity. The study population was delimited, and a sample corresponding to landscape units with changes in vegetation cover during the analyzed period was selected. Data collection was carried out using published land cover and land use data, enabling analysis. Spatial analysis techniques were applied, and maps were generated to visualize landscape changes. The results reveal a marked trend of conversion of forest areas to agricultural and livestock activities, as well as a concerning expansion of mining. There is a net loss of forests and flooded forests, with active conversion to other categories such as flooded areas, grasslands, and areas without vegetation. In conclusion, pressure on natural resources is evident, highlighting the importance of territorial planning policies that balance economic development with biodiversity conservation and ecosystem services. Sustainable land management and environmental management policies promoting balanced use of natural resources in the study area are recommended.